English Core Competencies, Basic Competencies, and Assessment for Junior High School in Curriculum 2013; between Facts and Hopes - Does Ichnatun Dwi Soenoewati (Register Journal, 2015)
This paper focuses on some problems faced by Junior High School English target teachers concerning with the content, formulation, and the order of Core Competencies (known as KI) and Basic Competencies (known as KD) and the assessment in K ‘13 (known as K’13). The material in K ‘13 is regarded as being arranged in balance covering the students attitude, knowledge, and skills competencies stressing on language skills as a means of communication to convey ideas and knowledge. Based on the K ‘13 implementation mentoring, 13 out of 15 teachers (87%) interpret the Core and Basic Competencies differently and most tend to be unclear. This happened due to the formulation, content, and order of the KIs/KDs which were illogical, in contrary to mind mapping, and confusing the target teachers. Moreover, the assessment system, especially attitude assessments are too complicated. These facts make the writer interested to discuss the English KIs/KDs and assessment for Junior High School in K ‘13; between Facts and Hopes.Keywords:  Core Competencies/Basic Competencies and assessment in K ‘13, revision of the formulation, content, order of core competencies and basic competencies, and the simplification of attitude assessment